Hubungan Active Learning Dan Critical Thinking Dengan IPK Mahasiswa Program Studi Kedokteran Fakultas Kedokteran Universitas Malikussaleh - Muhammad Sayuti; Sofwatul Marfiyah (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2023)
The application of problem based learning methods requires students to have active learning and critical thinking skills, where these abilities are factors that can affect students' GPA. This study aims to determine the relationship between active learning and critical thinking with the GPA of students of the Medical Study Program, Faculty of Medicine, University of Malikussaleh. This study was an observational analytic study using a cross sectional approach. Statistical analysis using the Spearman test. Sampling in this study using total sampling with a total of 274 students who have met the inclusion and exclusion requirements. The results of the univariate analysis of ability active learning and critical thinking of all respondents at the most at the ambivalent level of 262 respondents (95.6%), followed by high measurement results of 8 respondents (2.9%) and low measurement results of 4 respondents (1.5%). Icumulative achievement indexAll respondents were found at a very satisfactory level of 209 respondents (76.6%). GPA with praise of 50 respondents (18.3%). Satisfactory GPA of 14 respondents (5.1%). Bivariate statistical analysis get p value <0.05. The conclusion of this studythere is a relationship between active learning and critical thinking with the GPA of students of the Medical Study Program, Faculty of Medicine, University of Malikussaleh.